Microfluidic Synthesis of Carbon Nanotube-Networked Solid-Shelled Bubbles - Jun, Hyun Min (Langmuir : the ACS journal of surfaces and colloids, 2020)
Carbon nanotubes (CNTs) have attracted considerable attention because of their high electrical conductivity and outstanding mechanical properties. As such, there have been numerous attempts to form CNTs into diverse structures for use in a wide range of applications. However, the intrinsic high aspect ratios of CNTs and resulting deformability have prevented the fabrication of sophisticated CNT-based structures, especially for three-dimensional (3D) cellular architectures. To challenge this limitation, we present a novel method to fabricate a 3D CNT cellular network from the assembly of microfluidically synthesized CNT-shelled microbubbles. We successfully generated stable spherical CNT-shelled bubbles with excellent size and shape uniformity by precisely controlling bubble dimensions by varying microfluidic variables. We also developed a fundamental understanding of the bubble stability, which allowed us to suppress shrinkage-induced deformation. The synthesized CNT-shelled bubbles were assembled into a 3D close-packed structure, followed by treatment with thermal reduction to induce interfacial bonding and transformation into a closed cellular network structure. Overall, this work provides a new strategy of assembling 1D nanomaterials as the building blocks for well-regulated 3D closed cellular architectures with improved structural or physical properties